Comunidad Shuar y el turismo cultural en el cantón Bucay de la Provincia del Guayas - Mosquera Jarrin, Anahis Carolina (2019)
The Shuar culture is the most populated in Ecuador with more than 80 thousand inhabitants dispersed in the Ecuadorian Amazon and in the jungle of Peru, the objective of the case study is to strengthen the identity of the Shuar culture and convert its cultural resources into a heritage tourism, the loss of their cultural heritage, language, traditions, customs, costumes, their philosophical thinking has undergone major changes, predominant factors that have caused these losses is because external evangelical groups got involved with this ethnic group and the migration they made moving from the Ecuadorian Amazon to the coastal region. The Shuar indigenous culture is characterized by its strong traditions and a unique vision of the universe, which manifests itself through its language, food, myths, music and dance. Their ancestral territorial rights are guaranteed by the Constitution of Ecuador, but validating those rights and guaranteeing their legitimacy requires the support and action of public and private institutions. The indigenous commune and ascendants arrived 30 years ago from the province of Morona Santiago, in the East, to settle in this land and form the Shuar community, a town near the Bucay canton. They brought their customs, their clothes of colorful fabrics and feathers of birds that adorn with belts and necklaces of tree seeds, like the one they call Nupi, that move in each typical dance with which they welcome the visitor.